Social Forestry Regulation Post Job Creation Law: Utilizing Village Forest Potencies to Obtain Village SDGs Agenda - Zuhda Mila Fitriana; Dessy Maeyangsari; Dhea Veranica Isabella; Lupita Sari (Future Science, 2022)
Social forestry has been implemented for decades in Indonesia to escalate society’s welfare. In particular, it is designed to grow the economy of forest-surrounded village societies by utilizing forest natural resources in specific schemes such as Village Forest. Government Regulation No.6/2007 regarding Forest Management and Preparation of Forest Management Plans and Forest Utilization regulated that Village Forest is manageable by villages and exploitable for village welfare. The Job Creation Law (JCL) enactment now recognizes the existence of social forestry under Article 26 para (2) JCL. It is grounded in the notion that social forestry potentially supports the national investment climate and national SDGs Agenda, particularly the scheme of village forest utilization, as village governances contribute to more than 90% of national power. Based on that notion, the government introduced the SDGs Village Agenda, which is expected to contribute to most national targets. Applying normative legal research as the primary method with the empirical and conceptual approach, it is discovered that the well-utilization of village forests has escalated the IDM level, which also represents SDG’s Desa Agenda. The discussion covers the authority of the Village-Owned Enterprises (BUMDes) in utilizing village forest post-JCL, the ways of utilization, and the success story of villages – learning from Labbo Village, Bantaeng. Indeed, using the village forest supports the escalation of IDM Level and SDGS Agenda achievement.